2021
DOI: 10.3390/ijerph18020593
|View full text |Cite
|
Sign up to set email alerts
|

Equity of Health Services Utilisation and Expenditure among Urban and Rural Residents under Universal Health Coverage

Abstract: Worldwide countries are recognising the need for and significance of universal health coverage (UHC); however, health inequality continues to persist. This study evaluates the status and equity of residents’ demand for and utilisation of health services and expenditure by considering the three components of universal health coverage, urban-rural differences, and different income groups. Sample data from China’s Fifth Health Service Survey were analysed and the ‘five levels of income classification’ were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…This is consistent with the previous studies that suggested health inequality is a plausible explanation for the link between SES and health outcomes. 18 Previous research has also shown that the NHI system in a country has created a health gap based on income gaps, but according to the results of this study, 9 health status was significantly poor for the group alienated from the NHI and had a low educational level. It is estimated that the interaction effect for household income was not significant because eligibility for MA recipients in Korea is based on an individual’s income.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…This is consistent with the previous studies that suggested health inequality is a plausible explanation for the link between SES and health outcomes. 18 Previous research has also shown that the NHI system in a country has created a health gap based on income gaps, but according to the results of this study, 9 health status was significantly poor for the group alienated from the NHI and had a low educational level. It is estimated that the interaction effect for household income was not significant because eligibility for MA recipients in Korea is based on an individual’s income.…”
Section: Discussionmentioning
confidence: 47%
“… 8 In the case of China also, compared to high-income groups, lower-income groups faced higher hospitalization expenses under the universal health service, and health inequality continues to persist. 9 Therefore, it is questionable whether Korea’s NHI system is effective in reducing health disparities.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, poverty was an individual protective factor for aggressiveness with police dispatch or violent crime. This may be attributed to the higher rate of receiving regular follow-ups and increasing demand and utilization of health services among patients under the poverty lines [51,54].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, poverty was an individual protective factor for aggressiveness with police dispatch or violent crime. This may be attributed to the higher rate of receiving follow-ups regularly and increasing demand and utilization of health services among poverty patients [49,52].…”
Section: Discussionmentioning
confidence: 99%